Synthesis of Poly [Allylamine-Co-Butadiene] form reduction of Poly [Acrylonitrile-Co-Butadiene] and grafting the product with Amic acids - Al-Majidi, Suaad (Iraqi Journal of Science, 2025)
Pure Poly [Allylamine-Co-Butadiene] having high molecular weight was prepared for the first time from the reduction of the Poly [Acrylonitrile-Co-Butadiene] using Lithium Aluminium hydride. Softening point of the prepared polymer was (201-207)C, conversion percent was 88%, with intrinsic viscosity of the new polymer in benzene as a solvent was 1.56.Then the new polymer was allowed to react with six acid anhydrides, (Maleic, Phthalic, Succinic, Glutaric, 1,8-Naphthalic and cis 1,2,3,4-tetrahydrophthalic) to produce six novel pendant polymers which contain the acids reffered above in its recurrent units. The prepared poly [N-(ally)substituted amic acid-Co-butadiene] polymers were characterized using FTIR, H-NMR, and some specific tests.